Macro- and micro-nutrient intake of adolescent Greek female volleyball players - Papadopoulou, S. K.; Papadopoulou, S. D.; Gallos, G. K. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
Adequate nutrition is critically important for the achievement of the adolescent athlete's optimal performance. The purpose of the present study was to evaluate the adequacy of macro- and micro-nutrients in the adolescent Greek female volleyball players' diet. The subjects of the study consisted of 16 players who were members of the Junior National Team (NP) and 49 players who participated in the Junior National Championship (CP). Dietary intake was assessed using a 3-day food record. Protein intake (16.0 ± 4.9% of total energy intake) was satisfactory, whereas fat consumption (37.5 ± 11.1%) was above recommended values and at the expense of carbohydrate intake (45.9 ± 12.5%). There were no significant differences between NP and CP concerning the intake of macronutrients, except for the fat intake (when this is expressed in grams per day and grams per kilogram of body weight and the saturated fat intake, which were both higher in NP compared to CP players (p < .05). The mean energy intake was 2013 ± 971 and 1529 ± 675 kcal for NP and CP, respectively (p < .05). NP, in particular, consumed fat and especially saturated fat in order to meet their energy needs. As for micronutrients, the volleyball players fell short of meeting the RDA values for calcium, iron, folic acid, magnesium, zinc, and vitamins A, B1, B2, and B6. There was no difference between NP and CP in micronutrient intake. In conclusion, subjects in the current study lacked proper nutrition in terms of quantity and quality.